Guitar Too, for Four - Parra Cancino, Juan; Remembering Phill Niblock Orpheus Institute, Ghent 5 May, 2024 (2024)
Guitar, Electronics
Performance of "Guitar Too, for Four" by Phill Niblock."Remembering Phill Niblock"event. Different venues in Ghent.
FRIS
Editorial review
Keywords: Music, Thought and Technology